Orcokinin neuropeptides regulate ecdysis in the hemimetabolous insect Rhodnius prolixus - Wulff, Juan Pedro (2017)
To grow and develop insects must undergo ecdysis. During this process, the individual sheds the old cuticle to emerge as the following developmental stage. During ecdysis, different programed behaviors are regulated by neuropeptidergic pathways. In general, components of these pathways are better characterized in crustacean and holometabolous insects than in hemimetabola. In insects, the orkoninin gene produces two different neuropeptide precursors by alternative splicing: orcokinin A and orcokinin B. Although orcokinins are well conserved in insect species, their physiological role remains elusive. Here we describe a new splicing variant of the orcokinin gene in the hemimetabolous triatomine Rhodnius prolixus. We further analyze the expression pattern and the function of the alternatively spliced RhoprOK transcripts by means of immunohistochemistry and RNAi-mediated gene silencing. Our results indicate that orkoninis play an essential role in the peptidergic signaling pathway regulating ecdysis in the hemimetabolous insect Rhodnius prolixus.